INTERNALISASI NILAI-NILAI SPIRITUAL ISLAMI DALAM KEGIATAN PENDIDIKAN - Nirwani Jumala Nirwani Jumala; Abubakar Abubakar (JURNAL SERAMBI ILMU, 2019)
Students in Islamic schools are expected to achieve the indicators of spiritual intelligence that have been predefined in the Learning Implementation Plan. However, in reality the values internalized to obtain the spiritual competence have not been able to completely change the characters of the students.This study aimed to analyze and to evaluate the achievement indicators of Islamic spiritual value competence, the methods of internalizing Islamic spiritual values, and the factors influencing the internalization of Islamic spiritual values for the students at two private Madrasah Aliyah (Islamic senior high schools), Ruhul Islam Anak Bangsa and Darul Ihsan. The study used a qualitative approach, conducted in Ruhul Islam Anak Bangsa and Darul Ihsan from April 2016 to August 2018. Data collection techniques were interview, observation, self-assessment, peer assessment, and documentation. Data analysis was done by organizing and codifying the data, enriching the theory, interpreting data, and writing the report. Findings showed that in both schools the achievement indicators of Islamic spiritual values included instilling understanding and strengthening faith ('aqidah), initiating worship routines, showing steadfast (istiqāmah) and sincere (ikhlaṣ) attitudes in carrying out the practices of drawing close to Allah (taqarrub ilallāh), transforming bad behaviors into those that reflect religious values, displaying Islamic identity, and maintaining fraternity (ukhuwwah) in everyday life. The methods of internalizing these Islamic spiritual values were carried out by lecturing and religious gathering (halaqah), discussion (jadal), storytelling (qiṣṣah), dialogue (ḥiwar), conveying good messages (mau'iḍah al-hasanah), self-discipline (riyāḍah), role model (uswatun al-ḥasanah), conveying excellent rewards (tabsyir), outpouring thoughts and feelings (muḥāḍarah), encouragement and deterrence (targhib wa tarhīb), contemplation (tafakkur), pondering over (tadabbur), and concentration (tawajjuh). The success of internalizing the values was largely influenced by good relations between teachers and students, the learning methods applied, good learning environment conditions, adequate learning infrastructure and facilities, the commitment to the quality of education, and the participation of committees, founders, government, and stakeholders in the management of education. To conclude, value education should not separate spiritual and social attitudes. Social values can become spiritual when implemented under the teachings of the Qur'an and the Sunnah. The values that have been successfully internalized were those with a sense of well-being, such as the goodness rooted in a community.